Amyloid binding and beyond: a new approach for Alzheimer's disease drug discovery targeting Aβo–PrPC binding and downstream pathways. Issue 10 (1st February 2021) - Grayson, James D.; Baumgartner, Matthew P.; Santos Souza, Cleide Dos; Dawes, Samuel J.; El Idrissi, Imane Ghafir; Louth, Jennifer C.; Stimpson, Sasha; Mead, Emma; Dunbar, Charlotte; Wolak, Joanna; Sharman, Gary; Evans, David; et al.
Abstract : A new approach combining virtual screening, 19 F and STD NMR, and biochemical assays using hiPSC and targetting multiple pathways involving Aβ, PrP C and Tau provides a more effective strategy for Alzheimer's disease drug discovery than Aβ only approach. Abstract : Amyloid β oligomers (Aβo) are the main toxic species in Alzheimer's disease, which have been targeted for single drug treatment with very little success. In this work we report a new approach for identifying functional Aβo binding compounds. A tailored library of 971 fluorine containing compounds was selected by a computational method, developed to generate molecular diversity. These compounds were screened for Aβo binding by a combined 19 F and STD NMR technique. Six hits were evaluated in three parallel biochemical and functional assays. Two compounds disrupted Aβo binding to its receptor PrP C in HEK293 cells. They reduced the pFyn levels triggered by Aβo treatment in neuroprogenitor cells derived from human induced pluripotent stem cells (hiPSC). Inhibitory effects on pTau production in cortical neurons derived from hiPSC were also observed. These drug-like compounds connect three of the pillars in Alzheimer's disease pathology, i.e. prion, Aβ and Tau, affecting three different pathways through specific binding to Aβo and are, indeed, promising candidates for further development.